The state and international relations - Hobson, John M. (Themes in international relations., 2000)
This book provides a fresh overview of theories of the state found in International Relations. The author surveys realist, liberal, Marxist, constructivist and neo-Weberian approaches, and offers a unique introduction to the subject. The book will be of interest to students of sociology and politics, as well as International Relations.